An analysis of the relationship between personal values and satisfaction with work - Camfield, Claudio Eduardo Ramos; Borell, Diana Abreu Von; Rodrigues, Ricardo Gouveia (Revista de Administração da UFSM, 2019)
The objective of this study is to analyze the relationship between personal values and job satisfaction. For this, a multiple linear regression was made, whose independent variables were personal values and the dependent variable, job satisfaction. The data for this test were collected from the European Social Survey database (ESS, 2012) with a valid sample of 820 people (portugueses) who participated in a social survey which is applied annually in 20 European countries. From 4 assumptions made in the study, 3 were rejected, revealing that personal values and conservation of self-transcendence Don’t have positive relation with job satisfaction, as well as the self-promotion of value does not have a negative and significant relation as suggested. The value of openness to change, however, showed a negative and significant relationship at 5%. The results suggested that personal values did not possess relevant explanatory power on job satisfaction, in this sample. Therefore, we suggest the inclusion of other variables in the model to provide better contribution to the literature about this theme, as well as for managers where they consider relevant employee satisfaction with their work.